The Contribution of Waqf in Achieving Sustainable Education in Muslim Societies - Achmad Galih Pratama; Yosi Aryanti; Tira Karnesa (ASFA Foundation, 2026)
Throughout Islamic history, waqf has served as a vital institution supporting social welfare and education. In recent years, its potential has gained renewed attention as a sustainable mechanism to advance educational equity and quality within Muslim societies. This paper examines the contribution of waqf to achieving sustainable education, aligning with Sustainable Development Goal 4 (Quality Education). Using a qualitative and descriptive design, the study draws upon a broad review of literature and documented case studies from Indonesia, Malaysia, and other Muslim-majority nations. The analysis highlights that educational waqf not only enhances access to learning but also ensures long-term institutional resilience through continuous funding. Furthermore, emerging models such as productive and digital waqf demonstrate the adaptability of Islamic philanthropy to contemporary educational challenges. Despite existing obstacles in governance, policy, and public engagement, waqf remains a powerful driver for inclusive and sustainable education reform. The study concludes that strengthening collaboration among government bodies, educational institutions, and waqf managers, combined with the integration of digital financial innovations is essential to fully realize the transformative role of waqf in modern Muslim societies.